Effect of Bacillus sp. as probiotic on the treatment of environment in brackish water shrimp aquaculture. Issue 1 (December 2020) - Phung, L T; Phung, N K; Phuong, T T M; Nicolas, M; Vincent, M; Sandra, A; Philippe, D. S. J.
Abstract: In the face of increasing consumers demand for aquatic food products is to be safe and quality, requiring aquaculture farmers to strengthen preventive measures to limit the residues of chemicals and antibiotics in aquatic products, especially in the international markets. Therefore, the application of probiotics is considered to be the key to the success of aquaculture. In this work, we have studied probiotics produced from Bacillus, capable of treating environment in brackish water shrimp aquaculture. Apply 1x10 5 CFU/mL water treatment concentration, 5 days/time. Shrimp with mean initial weight of 0.034 g. There were two treatments in triplicates including 1) the control (without supplementing bacteria); 2) supplementing Bacillus subtilis. After 60 days, water quality parameters (DO, COD, TAN, NH3 and TSS) indicated that in the supplemental probiotic treatments had better decomposition of organic substances and lower Vibrio density than in the control treatments. Growth rate of shrimp in terms of daily weight gain and daily length gain were highest in treatment 2 (0.098±0.012 g/day) and 0.158±0.011 cm/day), and lowest in the control (0.078±0, 009g/day) and 0.121±0.012 cm/day). These results indicated that supplementation of these bacteria in the culture medium could promote a better decomposition of organic matter, help improve survival and growth rate of shrimp.